2009
DOI: 10.1111/j.1439-0310.2008.01579.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eavesdropping on Subsequent Signalling Behaviours in Male Canaries

Abstract: Signalling interactions could provide information for an observing third party. This behaviour has been labelled as eavesdropping. Studies on eavesdropping in birds have concerned only few species and have mainly been conducted in the wild. Our experiment was designed to evaluate the effects of eavesdropping on subsequent interactions in male canaries in a controlled laboratory context. The experiment had two stages: a presentation stage and a test stage. During the presentation stage, subjects heard three dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…These differential gains for winners and losses for losers are expected to be amplified when interacting in front of an audience, since not only the opponent but also the bystanders will gain information on the competitive ability of the interacting individuals (Peake & Mcgregor, 2004). The increasing number of studies that have reported that bystanders can eavesdrop on others' agonistic interactions and use the gathered information in subsequent interactions with the observed individuals (Amy & Leboucher, 2009;Earley & Dugatkin, 2002;McGregor, Peake, & Lampe, 2001;Oliveira, McGregor, & Latruffe, 1998;Peake, Terry, McGregor, & Dabelsteen, 2001) reinforce the idea that losing in front of conspecifics might come at a higher price. This asymmetry between winner and loser effects is also present in zebrafish (Oliveira et al, 2011) and hence may help to explain the observed decrease in overt aggression when interacting in the presence of the audience.…”
Section: Discussionmentioning
confidence: 95%
“…These differential gains for winners and losses for losers are expected to be amplified when interacting in front of an audience, since not only the opponent but also the bystanders will gain information on the competitive ability of the interacting individuals (Peake & Mcgregor, 2004). The increasing number of studies that have reported that bystanders can eavesdrop on others' agonistic interactions and use the gathered information in subsequent interactions with the observed individuals (Amy & Leboucher, 2009;Earley & Dugatkin, 2002;McGregor, Peake, & Lampe, 2001;Oliveira, McGregor, & Latruffe, 1998;Peake, Terry, McGregor, & Dabelsteen, 2001) reinforce the idea that losing in front of conspecifics might come at a higher price. This asymmetry between winner and loser effects is also present in zebrafish (Oliveira et al, 2011) and hence may help to explain the observed decrease in overt aggression when interacting in the presence of the audience.…”
Section: Discussionmentioning
confidence: 95%
“…Here, the timing of song learning is important: adult males only tolerate immature males within their territory, which suggests that opportunities for direct interactions may exist during early learning, while limited to eavesdropping later on [32]. In a laboratory setting, canaries that overheard overlapping songs between two males were less likely to call to the interrupting "winner" male at a later time [33]. This could mean that they perceive and remember dominance in singing interactions.…”
Section: Non-vocal Communicationmentioning
confidence: 99%
“…Suppose that bird A displaces bird B, but bird B displaces bird C: will the juvenile observer infer a linear hierarchy from those pairwise interactions [74], and use this information to alter its developing song? Such an inference could affect moment-to-moment behavior (e.g., deciding which virtual bird to approach or exchange calls with [33]) as well as developmental trajectories related to tutor choice and song convergence or divergence within the peer group.…”
Section: Toward Virtual Social Environments (Vses) For Studying Vocalmentioning
confidence: 99%
“…), territory ownership (López & Martín ), or fighting ability (McGregor et al. ; Earley & Dugatkin ; Amy & Leboucher ; Sprau et al. ).…”
Section: Introductionmentioning
confidence: 99%